High-resolution transcriptome analysis on a mouse model of neonatal hypoxic-ischemic encephalopathy using single-nucleus RNA-seq - Nao Wakui; Takashi Shimbo; Morifumi Hanawa; Tomomi Kitayama; Yukari Yamamoto; Yuya Ouchi; Kotaro Saga; Aiko Okada; Kazuya Mimura; Katsuto Tamai; Masayuki Endo (Biochemistry and Biophysics Reports)
Neonatal hypoxic-ischemic encephalopathy (HIE) encompasses brain injuries resulting from dysregulated oxygen or blood flow to the brain before, during, or immediately after birth. During the acute phase, neuronal damage is driven by excitotoxicity, with permanent injury manifesting over the subsequent hours. Treatment options have limited efficacy, requiring deeper insights into HIE pathogenesis. Recent advances in single-cell RNA sequencing have enabled molecular investigations of diverse diseases. However, the large size of certain cells, such as neurons, has posed challenges in studying conditions where neuronal damage is central. Thus, we employed single-nucleus RNA sequencing to evaluate damages in a mouse model of HIE and found pronounced changes in the hippocampus with significantly reduced neuronal populations. We observed the characteristic activation of hippocampal microglia, confirmed by immunostaining in the HIE model. These alterations were specific to combined hypoxic-ischemic conditions and were not observed with hypoxia or ischemia alone. These findings provide insights into the molecular and anatomical impact of HIE and highlight the hippocampus as a critical focus for understanding disease mechanisms and therapeutic development.